Uso del Poliacrilato de potasio en el cultivo de sandía (Citrullus lanatus). - Vergara Villegas, Rosa Elizabeth (2024)
In the development of this research based on the "Use of potassium polyacrylate in the cultivation of watermelon (Citrullus lanatus), in which the objective was established to characterize the benefit of potassium polyacrylate in the cultivation of watermelon (Citrullus lanatus). In terms of development, topics were taken such as potassium polyacrylate being a water retainer; origin of the watermelon crop, botanical description, climatic requirements of the crop, soil requirements, definition of potassium polyacrylate, use of polymers, chemical composition, how it works, the benefits of in watermelon cultivation. In the results, potassium polyacrylate in watermelon cultivation has proven to be beneficial. This water-retaining polymer reduces the need for frequent irrigation and ensures a constant supply of water for plants by improving water retention in the soil and soil aeration. In addition, hydrogel applications significantly improve soil water management by incorporating 1 to 2 g of hydrogel per kg/s in silty-clayey soils, and 2 to 3 g in sandy soils for optimization. In conclusion, the benefit of hydrogel is particularly valuable in soils with low water retention capacity where moisture control can make a big difference in plant health and productivity. To achieve better results, it should be incorporated where the seedling will be located at a depth of 2 to 3 cm and the dose should be applied evenly so that it can remain active for 4 to 7 years.